MEMPELAJARI PENGARUH KONSENTRASI DARI TEPUNG BUNGA KECOMBRANG (Nicolaia spesiosa Horan) SEBAGAI BAHAN PENGAWET ALAMI TERHADAP DAYA SIMPAN TAHU - Hadiansyah, Firman; Suyatno, Suyatno (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2014)
This study aims toStudy Effect ConcentrationOf Flour Flowers kecombrang (Nicolaiaspesiosa Horan) As Preservatives Natural to Power Save Know . This study was conducted in June 2014 to August 2014 in the laboratory of the Faculty of Agriculture, University of MuhammadiyahPalembang.The method used was a completely randomized design (RAL) are arranged in a non factorial with 5 (five) factor treatment concentration of flour kecombrang interest as a natural preservative know that repeated five (5) times. Each treatment with a concentration of as much as 0.00 % interest kecombrang0,00%,1%, 2%, 3%, 4%.The parameters observed in this study, for the analysis of the level of acidity (pH) and protein levels were tested before and after storage for 5 days and the visual observation of the odor, mold, slime and discoloration that occurs during the storage process. Organoleptic include,aroma, color and taste to know sebelumdan after 5 days of storage. of interest flour kecombrang significantly affect the color, aroma and flavor, to know before and after storage.Test storability visual observations to changes in smell , if there is mold , presence or absence of mucus and discoloration on out during 5 days of storage that has not changed is the T4 treatment (kecombrang interest flour concentration 4,00 %).